Testing Poincare invariance with QED - Spannowsky, Michael (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2024)
The principles of time and space translation invariance, which result in energy and momentum conservation, are among the most fundamental and widely accepted symmetry assumptions in physics. However, it is judicious to subject such assumptions to experimental and observational scrutiny. Thus, we initiate this process by specifying a simple periodic time dependence that contravenes time translation invariance in QED, and establishing phenomenological constraints on it. Besides observational and experimental constraints on time-varying couplings, we emphasise probes of energy conservation violation such as spontaneous photon and electron pair production and the e → e γ process.